Labour contracts and the stepping-stone effect in Emilia-Romagna: A multinomial analysis - Maria Giovanna Bosco; Elisa Valeriani (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Do short-term contracts facilitate the transition into permanent contracts? We use a rich administrative database for the Emilia-Romagna northern region in Italy from 2008 to 2012 to run a stepping-stone analysis and evaluate which contractual agreement is more likely to lead to a permanent working position. We find that individual specific characteristics make it more likely for a worker to be employed with a specific contractual agreement and that the contribution towards more working stability varies with the previous contract. We conclude that fixed-term positions act more as stumbling blocks than building blocks for open-ended contracts.
http://dx.doi.org/10.7910/DVN/1S0VPK
Keywords: J20; J21; J41; 330; Dependent labour; labour market institutions; career analysis